Organic Matter and Barium Absorption by Plant Species Grown in an Area Polluted with Scrap Metal Residue - Cleide Aparecida Abreu; Mariana Cantoni; Aline Renée Coscione; Jorge Paz-Ferreiro (Applied and Environmental Soil Science)
The effect of organic matter addition on Ba availability to Helianthus annuus L., Raphanus sativus L., and Ricinus communis L. grown on a Neossolo Litólico Chernossólico fragmentário (pH 7.5), contaminated with scrap residue was evaluated. Four rates (0, 20, 40, and 80 Mg ha−1, organic carbon basis) of peat or sugar cane filter, with three replicates, were tested. Plant species were grown until the flowering stage. No effect of organic matter addition to soil on dry matter yield of oilseed radish shoots was observed, but there was an increase in sunflower and castor oil plant shoots when sugar cane filter cake was used. The average Ba transferred from roots to shoots was more than 89% for oilseed radish, 71% for castor oil plants, and 59% for sunflowers. Organic matter treatments were not efficient in reducing Ba availability due to soil liming.